1990
DOI: 10.1093/jn/120.6.649
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Liver and Gastrointestinal Tract Energy Demands in Response to Physiological Workload in Ruminants

Abstract: Liver and gastrointestinal tract weights (ingesta- and adipose-free) appear to increase or decrease in direct proportion to dietary intake within and across physiological stages of maintenance, growth, fattening or lactation. Liver and gut mass increase approximately 15 and 30 g per unit of liveweight raised to the 0.75 power (Wt0.75) for each multiple of 500 kJ/Wt0.75 [approximately 1 x maintenance (M)] increase in metabolizable energy (ME) intake, with linearity indicated up to the highest recorded level (4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
113
1
8

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 35 publications
11
113
1
8
Order By: Relevance
“…Previous studies have demonstrated similar results (Yeh, 1983;Johnson et al, 1990;Sainz & Bentley, 1997;McLeod & Baldwin, 2000;D'Inca et al, 2010;Wang et al, 2005).…”
Section: Growth Of Tissuessupporting
confidence: 74%
“…Previous studies have demonstrated similar results (Yeh, 1983;Johnson et al, 1990;Sainz & Bentley, 1997;McLeod & Baldwin, 2000;D'Inca et al, 2010;Wang et al, 2005).…”
Section: Growth Of Tissuessupporting
confidence: 74%
“…At the tissue level, mass is related to its metabolism or functional workload (13,42), contributing 55-80% to the basal metabolic rate (reviewed in Refs. 31, 46, 60, and 81).…”
Section: Discussionmentioning
confidence: 99%
“…Assim, com a mobilização do tecido intestinal ou redução do turnover celular, o animal procura manter a homeostase energética. Johnson et al (1990) observaram, em ruminantes, que as vísceras, embora pesando menos de 10% do peso corporal, consomem de 40% a 50% do total de energia gasta pelo animal. Em aves reprodutoras, Sprat et al (1990) relataram que, embora o intestino, Tabela 3.…”
Section: Variáveisunclassified